Characterization of the Prognostic Values of the CXCR1-7 in Clear Cell Renal Cell Carcinoma (ccRCC) Microenvironment - Wu, Zhulin; Zhang, Yingzhao; Chen, Xiang; Tan, Wanjun; He, Li; Peng, Lisheng (Frontiers in Molecular Biosciences, 2020)
Background: As cancer immunotherapy has become a hot research topic, the values of CXC chemokine receptors (CXCRs) in tumor microenvironment have been increasingly realized. More and more evidence showed that the aberrant expression of CXCRs is closely related to the prognosis of various cancers. However, prognostic values and the exact roles of different CXCRs in clear cell renal cell carcinoma (ccRCC) have not yet been elucidated. Methods: To further evaluate the potential of seven CXCRs as prognostic biomarkers for ccRCC, multiple online analysis tools, including ONCOMINE, UALCAN (TCGA dataset), Kaplan-Meier Plotter, MethSurv, cBioPortal, GEPIA, Metascape, and TIMER databases, were utilized in our research. Results: The mRNA expression of CXCR4/6/7 was significantly increased in ccRCC patients, and all CXCRs are remarkably related to tumor stage or grade of ccRCC. Higher levels of CXCR3/4/5/6 expression were correlated with worse overall survival (OS) in patients with ccRCC, while higher expression of CXCR2 was associated with better OS. 23.14% mutation rate (118/510) of CXCR1-7 was observed in ccRCC patients, and the genetic alterations in CXCRs were related to worse OS and progression-free survival in ccRCC patients. Additionally, 53 CpGs of CXCR1-7 showed significant prognostic values. For functional enrichment, our results showed that CXCRs and their similar genes may be involved in cancer-associated pathways, immune process, and angiogenesis, etc. Besides, CXCRs were significantly correlated with multiple immune cells (e.g., CD8+ T cell, CD4+ cell, and dendritic cell). Conclusion: This study explored the potential prognostic values and roles of the CXCRs in ccRCC microenvironment. Our results suggested that CXCR4 and CXCR6 could be the prognostic biomarkers for the patients with ccRCC.